Metaphase karyotypes of Anopheles (Nyssorhynchus) darlingi Root and A. (N.) nuneztovari Gabaldón (Diptera; Culicidae) - Míriam Silva Rafael; Wanderli Pedro Tadei (Genetics and Molecular Biology, 1998)
Metaphase karyotypes of Anopheles (Nyssorhynchus) darlingi and Anopheles (N.) nuneztovari from Manaus and Highway BR-174 (Manaus-Boa Vista), State of Amazonas, and Macapá, State of Amapá, Brazil, showed 2n = 6. They consisted of a pair of metacentric (chromosome II) and a pair of submetacentric (chromosome III) autosomes as well as sex chromosomes X and Y. In the sex chromosomes, the X was acrocentric in A. darlingi and submetacentric in A. nuneztovari. The Y chromosome was pointed in both species. The chromosomes of A. nuneztovari were larger than those of A. darlingi except for the Y chromosome. A. nuneztovari showed size polymorphism in the X chromosome. Somatic pairing and a strong constriction around the centromeric region in chromosomes II and III were exhibited in both species. The secondary constriction was only detected in chromosome II of A. darlingi from the Manaus population and chromosome III from the Macapá population.